Databases and Web Sites for Neurogenetics. Issue 1 (15th September 2019) - Brody, Thomas
Abstract: The goal of neurogenetics is an understanding of the genetic basis of brain structure and function. Neurogenetics deals with multiple areas of investigation, including the genetic basis of neural induction, patterning, cell fate specification, neuron maturation, axonal and dendritic organization, synapse function, neural information processing, and learning and behavior. This appendix provides links to databases and other Web sites used by neurobiologists for discovery of information about genes and cellular networks involved in neural development and neuron function. Special care has been taken to curate sites involving model organisms, since great strides have been made using Drosophila and C. elegans for understanding neural development and function. Published 2019. U.S. Government.